2010
DOI: 10.1016/j.cct.2010.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Systems of support to increase colorectal cancer screening and follow-up rates (SOS): Design, challenges, and baseline characteristics of trial participants

Abstract: Background Screening decreases colorectal cancer (CRC) morbidity and mortality, yet remains underutilized. Screening breakdowns arise from lack of uptake and failure to follow-up after a positive screening test. Objectives Systems of Support to Increase Colorectal Cancer Screening and Follow-up (SOS) is a randomized trial designed to increase: (1) CRC screening and (2) follow-up of positive screening tests. The Chronic Care Model and the Preventive Health Model inform study design. Methods The setting is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…The interventions were effective for short-term but not long-term, follow-up. Several studies have described interventions aimed at increasing follow-up rates and showed mixed results [13,19,[27][28][29][30][31][32][33][34][35][36][37][38][39][40]. When the patient and physician's relations are good and based on clear communication and trust, the patient will be more likely to adhere to and fulfill the physicians' instructions [41,42].…”
Section: Repeated Automated Mobile Text Reminders For Follow-up Of Pomentioning
confidence: 99%
“…The interventions were effective for short-term but not long-term, follow-up. Several studies have described interventions aimed at increasing follow-up rates and showed mixed results [13,19,[27][28][29][30][31][32][33][34][35][36][37][38][39][40]. When the patient and physician's relations are good and based on clear communication and trust, the patient will be more likely to adhere to and fulfill the physicians' instructions [41,42].…”
Section: Repeated Automated Mobile Text Reminders For Follow-up Of Pomentioning
confidence: 99%
“…Some active intervention participants who did not screen after they received the mailed interventions received further support to complete CRC screening (brief phone assistance from a medical assistant, or this plus nurse navigation). A full description of the study design and results of the initial 2 year and subsequent 3 year interventions have been published [9,10,17].…”
Section: Setting and Participantsmentioning
confidence: 99%
“…Systems of Support to Increase Colorectal Cancer Screening (SOS) is an ongoing four-arm randomized trial that compares usual care (arm-1) to stepped intensity interventions that include more resources for each step: mailings alone (arm-2, a pamphlet about CRC screening choices, a number to call if colonoscopy or flexible sigmoidoscopy was preferred, and mailed fecal kits for those not calling); mailings plus telephone-based brief assistance (arm-3); or mailings, brief assistance, and more intense telephone-based nurse navigation [9]. Adherence to CRC screening over two years of the study was more than double that of usual care (51% to 65% depending on intervention intensity vs. 26% in usual care; P < .001) [10].…”
Section: Introductionmentioning
confidence: 99%
“…One of them approaches an intervention that make records of the patients that must be tracked, with the goal to ensure the referral process to the treatment and preparation of the patients to a complete the diagnostic test [44].…”
Section: Jessica T Defrank 2007mentioning
confidence: 99%